Referral-based transition to subsequent rehabilitation at home after stroke: one-year outcomes and use of healthcare services - Sebastian Lindblom; Malin Tistad; Maria Flink; Ann Charlotte Laska; Lena von Koch; Charlotte Ytterberg (BMC Health Services Research, 2022)
Abstract Background There is a lack of knowledge about patients’ journeys across the stroke care continuum, especially regarding the transition from inpatient to outpatient care and rehabilitation. Therefore, the aim of the present study was to explore and describe patterns of healthcare use over a one-year period, health outcomes at 3 and 12 months for patients following a referral-based transition to subsequent rehabilitation in the home, and the caregiver burden on their significant others. A further aim was to explore factors associated with the use of rehabilitation and healthcare after the referral-based transition to continued rehabilitation in the home for people recovering from a stroke. Methods Data regarding healthcare use during the first 12 months post-stroke was collected from the Region Stockholm computerized register. Data on patient characteristics, disease-related data, and functioning were retrieved drawn from medical records and questionnaires. Descriptive statistics were used to present healthcare use, participants’ characteristics, disease-related data, and patient functioning. Multivariable regression models were created to explore associations between the total number of outpatient contacts, total visits with the neurorehabilitation team, and the independent variables. Results The mean age for the 190 participants was 73 years for men and 78 years for women. Twenty-one participants (11%) had an acute rehospitalization within 30 days after discharge, and 41 participants (21%) were re-hospitalized within 90 days. Twenty-two (12%) of the participants had no visits with the neurorehabilitation team, 73 (39%) participants had 1–3 visits, 57 (30%) had 4–16 visits, and 38 (20%) had ≥17 visits. Female sex and length of hospital stay were associated with a higher number of visits with the neurorehabilitation team. Living alone, higher self-rated recovery, and being able to walk independently were associated with a lower number of visits with the neurorehabilitation team. Female sex, having home help services before the stroke, longer length of hospital stay, and more comorbidities were associated with a higher number of outpatient contacts. Conclusions The findings indicate that there is no generic pattern of healthcare use during the first-year post-stroke in patients receiving referral-based transition to continued rehabilitation in the home. The different patterns of healthcare use seemed to mirror the participants’ level of functioning. However, there is a need to further investigate how follow-up and rehabilitation correspond to the needs of patients and their significant others in the short- and long-term perspective. Trial registration ClinicalTrials.gov , registration number: NCT02925871 . Date of registration: October 6, 2016.